Lyrics Training website to enhance A2 students’ listening comprehension skill - Medina Martínez, Tania Judith (2023)
Even though students have studied the English language for a few years, they still have trouble using the target language in real-life listening circumstances. Therefore, it is crucial to contribute with the educational area by incorporating musical activities like the Lyrics Training website, since good listening comprehension is essential among A2 level students of the Santa Rosa Educational Unit. The main objective of this research project is to implement the Lyrics Training website as an educational tool that improves listening comprehension ability of A2 students, so this objective will be achieved with the review of the relevant bibliographic material. The creation of a list of songs with omitted words in the lyrics to be applied in the experimental group and the results obtained after the analysis of the data. The present study intends to be quasi-experimental, the approach will be qualitative-quantitative and it will also be of an exploratory level since it seeks the probable reasons for the events based on the cause-effect relationships, through hypothesis testing. Likewise, it will be descriptive because it tends to interpret data between the variables related to the research topic. In addition, the socio-educational modality will be used and the instruments to be used are a pre and post-test. Finally, once this research project is completed, it is expected to find reliable bases regarding the increase of accurate listening comprehension skill.